Nanoparticle-drug conjugates treating bacterial infections - Jelinkova, Pavlina; Mazumdar, Aninda; Sur, Vishma Pratap; Kociova, Silvia; Dolezelikova, Kristyna; Jimenez, Ana Maria Jimenez; Koudelkova, Zuzana; Mishra, Pawan Kumar; Smerkova, Kristyna; Heger, Zbynek; Vaculovicova, Marketa; Moulick, Amitava; et al. (Journal of controlled release, 2019)
The ever increasing scenario of bacterial resistance against commonly available antibiotics is becoming a global threat of major concern, which necessitates the development of new strategies to overcome this hurdle. Conjugation of nanoparticles (NPs) with antimicrobial moieties, such as antibiotics, peptides or different biomolecules, has been one of the successful techniques in targeting antibiotic resistance. This review mainly focusses on the possible nanoparticle-drug conjugates with their activity against pathogenic bacterial infections. Nanoparticles play an array of roles, e.g. as a carrier, synergistically acting agent and as theranostic agent, henceforth facilitates the efficacy of therapy. Moreover, this review elaborates the studies with reported nanoparticles-drug conjugates that include their possible synthesis methodologies and applications. In most of the cases, the nanoparticles were found to increase the permeability of bacterial cell membrane, which enables higher uptake of antibiotics inside the bacterial cells which in return showed better effects. Even the conjugates were found to efficiently kill the antibiotic-resistant strains. Since several limitations are exerted by the biological systems, there is an urge for the advancement of nanoparticle-drug conjugates for better proficiency.
Keywords: Nanoparticles; Bacterial Infections; Animals; Humans; lidé; Antimicrobial peptide; zvířata; antibakteriální látky; Anti-Bacterial Agents; Resistance; Bacteria; Composites; Nanoparticle; Antibiotics; nanočástice; bakteriální infekce